2009
DOI: 10.1080/03670240802034996
|View full text |Cite
|
Sign up to set email alerts
|

Wild Edible Plants Used by the People of Manang District, Central Nepal

Abstract: Plant diversity plays an important role in maintaining the world's foods demands. Even today in Manang, a remote, mountainous district within the Annapurna Conservation Area, Nepal, local people gather substantial amounts of wild plants to meet their daily nutritional needs, with several species also used for trade. There has been little documented regarding the use of these wild foods, which play a part in both daily nutrition, and survival during times of famine. Moreover, planning for development, land use,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 19 publications
3
36
2
Order By: Relevance
“…This is probably because leaves are easy to collect compared with roots, flowers, and fruits (Giday et al 2009, Telefo et al 2011. This observation may also be due to the fact that leaves are the main photosynthetic organs containing photosynthates, which might be responsible for active principles (Bhattarai et al 2006). In this respect, many studies have reported the medicinal properties of extracts from leaves.…”
Section: Plant Parts and Manner Of Usementioning
confidence: 99%
See 3 more Smart Citations
“…This is probably because leaves are easy to collect compared with roots, flowers, and fruits (Giday et al 2009, Telefo et al 2011. This observation may also be due to the fact that leaves are the main photosynthetic organs containing photosynthates, which might be responsible for active principles (Bhattarai et al 2006). In this respect, many studies have reported the medicinal properties of extracts from leaves.…”
Section: Plant Parts and Manner Of Usementioning
confidence: 99%
“…The use of plant parts may make the species vulnerable unless they are harvested sustainably (Bhattarai et al 2006). Indeed, the reported use of the whole plant and the roots may be prejudicial for plant stability or propagation (Cunningham 2001) compared with the use of aerial organs (e.g., leaves, fruits, and seeds) because these plant structures are renewable (Sheldon et al 1997).…”
Section: Conservation Of Antidiabetic Plant Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mustang at least 70 species are used for medicine by amchis, Tibetan doctors [26], while more than one hundred NTFP species are consumed by the local people of Mustang [36]. The collection, use and sale of NTFP is widespread also in other districts such as Manang [37]. In Jharkot, NTFPs contribute to increase the opportunity space of productive activities and offer occupational alternatives in lean seasons.…”
Section: Flexibility Of Typementioning
confidence: 99%